Adverse effects associated to the application of ultrasound-guided percutaneous needle electrolysis - F., Valera Garrido; F., Minaya Muñoz; P., Ramírez Martínez; F., Medina i Mirapeix (Revista Fisioterapia Invasiva / Journal of Invasive Techniques in Physical Therapy, 2019)
Background Percutaneous needle electrolysis is a technique of invasive physical therapy which is increasingly used by physical therapists in their clinical practice. However, to date, no studies have analyzed the presence of adverse effects.The aim of the present study was to evaluate the incidence of adverse effects and the associated impact of the application of ultrasound-guided percutaneous needle electrolysis in disorders of the neuro-musculoskeletal system.Material and Method A prospective case series study was performed over a period of six months at the Sannus Clinic center (Madrid). A sample of patients was identified and recruited, and follow-up was performed up to six months after discharge. Initial information was collected regarding demographic data (age and sex) and clinical data (affected structure, area, type of pain and process associated to the pathology). During each of the sessions performed, percutaneous needle electrolysis was applied in an isolated manner and data were gathered on the treatment received, as well as the presence of any adverse effects. An adverse effect was considered as being any incident related with the application of percutaneous needle electrolysis which caused any damage, as perceived by both the patient and the physical therapist who applied the treatment. The type of adverse effect was recorded (pain, bleeding, hematoma, post-intervention vegetative reactions [sweating, pallor, abdominal discomfort], syncope, skin lesions, damage to organs, nerve lesions, pneumothorax, metal allergy), the moment these appeared (during application, after application, days after the application), its severity (transitory (<48h), reversible (resolved at discharge), irreversible), its impact (did not require any specific intervention, required an additional specific physical therapy intervention, required intervention from medical staff (without hospitalization), and cause (insufficient skill with the technique, malpractice, inappropriate protocol). The adverse effects were classified as mild or severe depending on whether or not an intervention was required.Results 214 patients (60.7% men; 39.3% women) received a total of 772 sessions, the mean number (and standard deviation) of sessions was 3.6 (1.1). The totality of patients treated with ultrasound-guided percutaneous electrolysis received more than one session, according to the methodology described by Valera & Minaya. The main reasons for consultation were tendinous pathologies (70.5%), muscle pathologies (11.7%), ligaments (6.5%), joint capsule-synovia (5.6%), nerve entrapments (4.2%) and others (1.4%). Degenerative processes were more common than acute inflammatory processes. The greatest incidence was in the lower limbs. Degenerative processes were significantly more frequent than tendinous problems. During the 772 sessions of ultrasound-guided percutaneous needle electrolysis, the most common adverse effects were pain during the intervention (96.1%) and in the days following treatment (71.1%), as well as mild vasovagal responses post-intervention (80.1%). One syncope was recorded (0.13%). All the effects were transitory and without impact. No hematomas were detected in the days after a mild bleeding, when this occurred (9.3%). Interventions were performed on the thorax in 1.5% of the procedures, close to organs (0.5%) or close to peripheral nerves (4.2%) without any adverse effect. In the 6-week follow-up after discharge no adverse effects were detected.Conclusions Percutaneous needle electrolysis is a safe technique. The adverse effects provoked by the application of percutaneous needle electrolysis are mild, transitory, without impact on the person's health and following a homogenous pattern. The pain and the mild vasovagal response associated with the intervention are frequent and inherent to the stimulus generated by the needling and the electric current employed.Introducción La electrolisis percutánea es una técnica de Fisioterapia Invasiva cada vez más empleada en la práctica clínica por parte de los fisioterapeutas, sin embargo, no existe hasta el momento estudios que hayan analizado la presencia de efectos adversos. El objetivo del presente estudio fue evaluar la incidencia de efectos adversos y su impacto asociado a la aplicación de la electrolisis percutánea ecoguiada en alteraciones del sistema neuromusculoesquelético.Material y Método Estudio prospectivo de serie de casos durante un periodo de 6 meses en el centro Sannus Clinic (Madrid). Se identificó y reclutó una muestra de pacientes, realizándose un seguimiento de 6 semanas tras el alta. Inicialmente se recopiló información relativa a datos demográficos (edad y sexo) y clínicos (estructura afectada, zona y tipo de dolor y proceso asociado a la patología). En cada una de las sesiones realizadas, se aplicó de forma aislada la electrolisis percutánea y se recogieron datos del tratamiento recibido, así como la presencia de efectos adversos. Se consideró efecto adverso cualquier incidente relacionado con la aplicación de la electrolisis percutánea que causara daño, según la percepción del paciente y fisioterapeuta que la aplicó. Se registró el tipo de efecto adverso (dolor, sangrado, hematoma, reacciones vegetativas post-intervención [sudoración, palidez, malestar abdominal], síncope, lesiones cutáneas, lesión de órganos, lesión nerviosa, neumotórax, alergia metal), su momento de aparición (durante la aplicación, después de la aplicación, días sucesivos a la aplicación), su severidad (transitorio (<48h), reversible (solución al alta), irreversible), su impacto (no requirió ninguna intervención específica, necesitó de intervención adicional específica de fisioterapia, necesitó de intervención personal médico (sin ingreso), ingreso hospitalario) y la causalidad (habilidad insuficiente con la técnica, mala praxis, protocolo inadecuado). Se clasificaron los efectos adversos en leves o graves dependiendo de si requería o no alguna intervención.Resultados 214 pacientes (60.7% hombres; 39.3% mujeres) recibieron un total de 772 sesiones, siendo el número medio (y desviación típica) de sesiones de 3.6 (1.1). A la totalidad de los pacientes tratados con electrolisis percutánea ecoguiada se les aplicó más de una sesión siguiendo la metodología descrita por Valera & Minaya. Los principales motivos de consulta fueron patologías tendinosas (70.5%), musculares (11.7%), ligamentaria (6.5%), capsular-sinovial (5.6%), atrapamiento nervioso (4.2%) y otros (1.4%). Los procesos degenerativos fueron más frecuentes que los inflamatorios de carácter agudo. La mayor incidencia fue en miembros inferiores. Los procesos degenerativos se presentaron significativamente más en los problemas tendinosos. En las 772 sesiones de electrolisis percutánea ecoguiada los efectos adversos más frecuentes fueron el dolor durante la intervención (96.1%) y en los días posteriores (71.1%), así como respuestas vasovagales leves post-intervención (80.1%). Se registró un síncope (0.13%). Todos los efectos fueron transitorios sin impacto. No se detectaron hematomas en los días siguientes tras el leve sangrado cuando se produjo (9.3%). El 1.5% de las intervenciones se llevaron a cabo sobre el tórax, en la proximidad a órganos (0.5%) o nervios periféricos (4.2%) sin ningún efecto adverso. En el seguimiento a las 6 semanas tras el alta no se detectaron efectos adversos.Conclusiones La electrolisis percutánea es una técnica segura. Los efectos adversos provocados por la aplicación de la electrolisis percutánea son leves, de carácter transitorio, sin impacto para la salud del paciente y siguen un patrón homogéneo. El dolor y la respuesta vasovagal leve asociada a la intervención son frecuentes e inherentes al estímulo generado por la punción y la corriente eléctrica empleada.
Keywords: percutaneous needle electrolysis; adverse effects